Thiomers: A Blessing to Evaluating Era of Pharmaceuticals. (5th July 2015) - Hanif, Muhammad; Zaman, Muhammad; Qureshi, Sundas
Abstract : Thiomers are the polymers modified for the mucoadhesive properties and other additive properties by incorporating thiol moieties in the backbone of the unmodified polymeric chain by substitution reactions or simple oxidation reactions. Drugs that are less soluble and permeable can be complexed with thiomers for their increased absorption through the mucosal membranes by increase in contact time and prolonged stay in body due to mucoadhesion. Immobilization of thiol group therefore increases the mucoadhesive properties of the modified polymer by 2–140-folds. The prepared thiomers are characterized and made stable by different techniques. Thiomers also give the controlled delivery of the active pharmaceutical ingredients in the body. Different polymers that are modified by thiolation are chitosan, polyacrylic acid, sodium alginate, sodium carboxy methyl cellulose, guar gum, and so forth. Thiomeric formulations are a challenge to deliver drugs with low therapeutic compatibility. Micro- and nanopreparations containing thiomers can be prepared by different techniques such as covalent crosslinking, in situ gelation, radical emulsion polymerization, and emulsification. Nowadays thiomers have wide range of applications as a promising pharmaceutical excipient in the evaluating era of pharmaceutical technology.